2012
DOI: 10.1093/nar/gks1259
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuous behaviour of archaeal ribosomal proteins: Implications for eukaryotic ribosome evolution

Abstract: In all living cells, protein synthesis occurs on ribonucleoprotein particles called ribosomes. Molecular models have been reported for complete bacterial 70S and eukaryotic 80S ribosomes; however, only molecular models of large 50S subunits have been reported for archaea. Here, we present a complete molecular model for the Pyrococcus furiosus 70S ribosome based on a 6.6 Å cryo-electron microscopy map. Moreover, we have determined cryo-electron microscopy reconstructions of the Euryarchaeota Methanococcus igneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 52 publications
1
88
1
1
Order By: Relevance
“…In mutant eL19 1–154 , the C-terminal 35 amino acid residues were removed, eliminating the bridge forming region in which eL19 interacts with 18S RNA ES6S and ribosomal proteins eS7 and uS17. Mutant eL19 1–146 , harbouring a deletion of 43 amino acid residues, mimicked the archaeal version of eL19 12 . In mutant eL19 1–133 , the entire C-terminal α-helix (56 amino acid residues) was deleted.…”
Section: Resultsmentioning
confidence: 98%
“…In mutant eL19 1–154 , the C-terminal 35 amino acid residues were removed, eliminating the bridge forming region in which eL19 interacts with 18S RNA ES6S and ribosomal proteins eS7 and uS17. Mutant eL19 1–146 , harbouring a deletion of 43 amino acid residues, mimicked the archaeal version of eL19 12 . In mutant eL19 1–133 , the entire C-terminal α-helix (56 amino acid residues) was deleted.…”
Section: Resultsmentioning
confidence: 98%
“…Cryo-electron microscopy-based studies recently reported that L7Ae, first identified as a large rRNA-associated subunit, has a second binding site on the small rRNA subunit and even a third site on the large rRNA (59). However, this third site appears to be missing in ribosomes of late branches of euryarchaea (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…An initial data set of ∼192,000 particles was sorted using several rounds of classical two-dimensional classification protocols implemented in RELION. Then, a 3D-classification in RELION using a 70 Å filtered map of the archaeal 30S (extracted from the Pyrococcus furiosus 70S structure48) helped to isolate several well-resolved classes that were used for further 3D classification. The following sorting procedure allowed us to discard classes without or with poorly resolved aIF1, aIF1A or tRNA.…”
Section: Methodsmentioning
confidence: 99%
“…The structures of the head and body parts of the 30S subunits were extracted from the P. furiosus 70S coordinates48 (PDB entry 4V6U). The head and body were manually placed independently into the electron density map using Chimera, before automatically refining the position in the same programme.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation